2001
DOI: 10.1177/10780870122184993
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Justice and Southern California’s “Riskscape”

Abstract: Past research on “environmental justice” has often failed to systematically link hazard proximity with quantifiable health risks. The authors employ recent advances in air emissions inventories and modeling techniques to consider a broad range of outdoor air toxics in Southern California and to calculate the potential lifetime cancer risks associated with these pollutants. They find that such risks are attributable mostly to transportation and small-area sources and not the usually targeted large-facility poll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
57
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 303 publications
(59 citation statements)
references
References 32 publications
2
57
0
Order By: Relevance
“…Macrosocial experiences over the life course create differential exposure to chemical, physical, and psyschosocial stressors for racial/ethnic and economically disadvantaged populations in areas known as “riskscapes” [23]. According to Wilson [2], “unhealthy community ecosystems” are a consequence of spatiotemporal disparities that operate through neighborhood segregation.…”
Section: Introductionmentioning
confidence: 99%
“…Macrosocial experiences over the life course create differential exposure to chemical, physical, and psyschosocial stressors for racial/ethnic and economically disadvantaged populations in areas known as “riskscapes” [23]. According to Wilson [2], “unhealthy community ecosystems” are a consequence of spatiotemporal disparities that operate through neighborhood segregation.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, unhealthy geographies that concentrate environmental, social, and health risks in urban and rural areas are produced and are known as ‘riskscapes’ [3,4]. The original Toxic Waste and Race in America report published in 1987, was the first report to demonstrate that many economically underserved populations and people of color communities are disproportionately impacted by locally unwanted land uses (LULUs) [5].…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has also shown that populations of color and low-income groups living in poor environmental conditions have health risks due in part to various social determinants of health including segregation, racism, socioeconomic status (SES), income inequality, and inequities in planning and zoning [1-4,6,14,19,20,28-31]. Studies have shown that underlying social and economic vulnerabilities contribute to increased health disparities [29,31,32], which further enhance the long-term effects of environmental injustice.…”
Section: Introductionmentioning
confidence: 99%
“…They point to a “double jeopardy” of environmental injustice in which the people with the fewest social, economic and political resources experience the greatest concentrations of environmental threats to their health and well-being [18] In particular, factors such as historical patterns of housing segregation, limited political and social capital, and policy processes that are inaccessible by grassroots constituencies have been shown to combine to create a “risks-cape” that systematically places communities with lower incomes and greater concentrations of people of color in harm’s way from a wide range of environmental hazards [18,19,20,21]. In the face of these conditions, activists call for three dimensions of environmental justice: distributional justice for addressing disproportionate burdens of environmental hazards and the absence of environmental goods, procedural justice for meaningful access to decision-making, and cognitive justice to consider local knowledge legitimate in the assessment and mitigation of environmental hazards [22,23].…”
Section: Introductionmentioning
confidence: 99%